1998
DOI: 10.1002/(sici)1096-9888(199806)33:6<505::aid-jms662>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase fragmentation of protonated mono-N-methylated peptides. Analogy with solution-phase acid-catalyzed hydrolysis

Abstract: Fragmentation of protonated peptides with a single N‐methylated residue was studied by low‐energy collision‐induced dissociation (CID) and the effects of the N‐alkylation on the fragmentation were evaluated. Peptides with an N‐terminal N‐alkylated amino acid behave similarly to regular peptides except for an increased stability of the protonated molecular ion due to the increased proton affinity. On the other hand, the N‐alkylation of an internal amino acid residue has very distinct effect on fragmentation. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 7 publications
(7 reference statements)
4
67
0
Order By: Relevance
“…A number of experimental measurements [14,15,[45][46][47][48] indicate that indeed charge transfer in proteins is labile. Some theoretical calculations [49 -51] also indicate that proton migration along the backbone may be a likely mechanism for charge transfer.…”
Section: Application Of the Coulomb Repulsion Modelmentioning
confidence: 99%
“…A number of experimental measurements [14,15,[45][46][47][48] indicate that indeed charge transfer in proteins is labile. Some theoretical calculations [49 -51] also indicate that proton migration along the backbone may be a likely mechanism for charge transfer.…”
Section: Application Of the Coulomb Repulsion Modelmentioning
confidence: 99%
“…The typical b n ion structure produced when a charge induces cleavage is an oxazalone. This protonated oxazalone forms when a backbone carbonyl oxygen attacks°an°electropositive°backbone°carbonyl°carbon° [47][48][49][50][51][52]°(Scheme°2).°It°is°not°clear°what°structure°the°b n ions have in the absence of an added proton. The lack of *a n ions°observed°in°Figure°4a°indicates°the°*b n ions observed by selective cleavage do not have the same *b n structure as formed from P ϩ LDIFSDF(OMe) 3 and suggests the ions are forming in a mechanistically different manner.…”
Section: Fragmentation Of P ϩ Ldifsdf and P ϩ Ldifsdf(ome)mentioning
confidence: 99%
“…The Asp acidic hydrogen can be considered mobile "locally" in this mechanism because it is transferred to the backbone carbonyl or amide nitrogen during formation of the anhydride b-ion. This anhydride b-ion differs from the "typical" b-ion structure formed when a backbone carbonyl oxygen attacks an electropositive backbone carbonyl carbon to form a protonated oxazalone structure [47][48][49][50][51][52], as shown Scheme 2.…”
mentioning
confidence: 98%
“…Amide nitrogen methylation occurs in nature, such as in bacterial and fungal peptides/proteins that have possible medicinal properties [14 -17], and has been used as a tool for protein binding studies [18]. The dissociation behavior of N-methylated peptide ions subjected to collisional activation has been reported, and it was noted that there was an increase in relative abundance of the products coming from cleavage of the amide bond at the methylation site [19,20]. It was suggested that this preferred cleavage occurred due to the increased basicity of the amide nitrogen.…”
mentioning
confidence: 99%